Efektivitas Konseling Individual melalui Pendekatan Konseling Rasional Emotif dalam Mengatasi Kecemasan - Indah Etika Putri; Zulfani Sesmiarni; Alfi Rahmi (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2021)
The aim of this research is to find out the effectiveness of individual counseling through emotive rational counseling approach in overcoming anxiety in Payakumbuh Class IIB Penitentiary. The population is fostered citizens before the criminal period ends as many as 20 people, while the study sample is fostered citizens before the criminal period ends as many as 5 people and who are indicated to have high anxiety based on non-rondom sampling techniques and recommendations from employees. The data collection instrument is a Likert scale. Data analysis techniques using non-parametric statistical tests using Wilcoxon rack test, hypothesis testing using Statistical Product and Service Solution (SPSS) version 22. The results showed the difference between the pretest and posttest values. From the Wilcoxon test calculation results obtained a significant sip-value of 2.023. Based on the applicable provisions, it is known that the Wilcoxon Sig p-value test result is 0.043 <α (α = 0.05) which means that Ha is accepted and Ho is rejected. From the results of the Wilcoxon test calculation it can be concluded that it is effective to overcome anxiety in the target population before the criminal period expires.